Epigenetic regulation of ecotype-specific expression of the heat-activated transposon ONSEN - Nozawa, Kosuke; Masuda, Seiji; Saze, Hidetoshi; Ikeda, Yoko; Suzuki, Takamasa; Takagi, Hiroki; Tanaka, Keisuke; Ohama, Naohiko; Niu, Xiaoying; Kato, Atsushi; Ito, Hidetaka (Frontiers in Plant Science, 2022)
Transposable elements are present in a wide variety of organisms; however, our understanding of the diversity of mechanisms involved in their activation is incomplete. In this study, we analyzed the transcriptional activation of the ONSEN retrotransposon, which is activated by high-temperature stress in Arabidopsis thaliana. We found that its transcription is significantly higher in the Japanese ecotype Kyoto. Considering that transposons are epigenetically regulated, DNA methylation levels were also analyzed, revealing that CHH methylation was reduced in Kyoto compared to the standard ecotype, Col-0. A mutation was also detected in the Kyoto CMT2 gene, encoding a CHH methyltransferase, suggesting that it may be responsible for increased expression of ONSEN. CHH methylation is controlled by histone modifications through a self-reinforcing loop between DNA methyltransferase and histone methyltransferase. Analysis of these modifications revealed that the level of H3K9me2, a repressive histone marker for gene expression, was lower in Kyoto than in Col-0. The level of another repressive histone marker, H3K27me1, was decreased in Kyoto; however, it was not impacted in a Col-0 cmt2 mutant. Therefore, in addition to the CMT2 mutation, other factors may reduce repressive histone modifications in Kyoto.